Mobilité durable : réfléchir la responsabilité sociale des entreprises à partir de l’éthique des capabilités - Benoit Genest (VertigO)
In reaction to the cost-benefit analysis approach (CBA) inspired by the utilitarian tradition, authors began as early as the 1970s to focus on the relationship between social justice and transportation. This concerns mostly deals with the mitigation of negative externalities and socio-economic impacts of transport infrastructure projects on various categories of population with, first and foremost, people with low mobility. Various analytical frameworks have begun to incorporate the work of John Rawls and, more recently, the two leading representatives of the Capability Ethics, Amartya Sen and Martha Nussbaum. While recent work has shed light on the relationship between mobility and human development, it has focused on the responsibility of governments vis-à-vis citizens. However, this approach neglects the role of the company in its ability to provide sustainable mobility solutions. This article proposes to demonstrate that the company can contribute positively to sustainable mobility by drawing on the principles of capabilism. These solutions can target both human resources and society from a dual perspective of distributed responsibility and institutional governance.